Retroperitoneal Femoral Nerve Reconstruction in the Pediatric Population. (June 2016) - Kattan, AE; Tsoi, K; Stubenitsky, Bm; Curtis, CG; Gerstle, JT; Clarke, HM
BACKGROUND: Retroperitoneal femoral nerve lesions in children are rare. They can result in a complete femoral nerve palsy causing severe functional impairment of ambulation and standing and sensory impairment of the anterior and medial thigh extending down the medial aspect of the leg. While treatment can be challenging due to the complex anatomy of the region and the difficulty of achieving adequate surgical access, femoral nerve repair has lead to the recovery of useful function in adult patients. OBJECTIVE: The authors review their experience from the surgical treatment of three consecutive cases of this rare lesion in children while focusing on validated outcome measures. METHODS: A retrospective chart review of all cases of retroperitoneal femoral nerve transection treated surgically was completed (n=3). Data collected included demographics, timing of repair, surgical approach, Medical Research Council muscle grading scores, the Hospital for Sick Children Active Movement Scale scores and follow-up period. RESULTS: Follow-up ranged from two to 4.5 years. All three patients had excellent motor recovery and ambulated without assistance. Sensory function also improved, with a substantial resolution of preoperative dysesthesia in one case. There were no major complications. CONCLUSIONS: Complete retroperitoneal femoral nerve transection in children is a rare but devastating injury. Appropriate surgical access to the retroperitoneal space is a prerequisite for lumbar plexus reconstruction and mandates a team approach. In the present series, all patients regained excellent function following reconstruction. The surgical treatment of these unusual lesions in childhood proved highly rewarding.